High-resolution phase mapping with parallel Fourier domain optical coherence microscopy for dispersion contrast imaging - Grajciar, Branislav; Herdin, Melanie; Blatter, Cedric; Gröschl, Martin; Leitgeb, Rainer A. (Photonics Letters of Poland, 2011)
We demonstrate a high-speed parallel line field optical coherence microscopy (OCM) system that exhibits intrinsically high phase stability even with lateral scanning. The presented Fourier domain (FD) OCM system employs a high speed CMOS detector and achieves up to 512 000 equivalent A-scans per second. The microscopy system is shown to resolve the smallest elements of the USAF resolution test target (Group 7, Element 6), indicating the transverse (Y- non-scanning parallel direction)) resolution and resolution in X (scanning) direction less than 2.2 µm. The capability of imaging biological samples is demonstrated on human red blood cells (RBC). The high phase sensitivity allows resolving the thickness map of the RBC. Resolving the phase gives further access to the dispersion properties of the sample, which in turn reveals chemical information of the microsystem. Full Text: PDF References W. Drexler, J.G. Fujimoto, Optical Coherence Tomography: Technology And Applications (Springer, 2008)[CrossRef] J.A. Izatt, M.R. Hee, G.M. Owen, E.A. Swanson, J.G. Fujimoto, "Optical coherence microscopy in scattering media", Opt. Lett. 19, 590 (1994)[CrossRef] A. Dubois, K. Grieve, G.Moneron, R. Lecaque, L. Vabre, C. Boccara, "Ultrahigh-Resolution Full-Field Optical Coherence Tomography", Appl. Opt. 43, 2874 (2004)[CrossRef] B. Grajciar, M. Pircher, A. F. Fercher, R. A. Leitgeb, "Parallel Fourier domain optical coherence tomography for in vivo measurement of the human eye", Opt. Exp. 13, 1131 (2008)[CrossRef] Y. Chen, S.W. Huang, A.D. Aguirre, J.G. Fujimoto, "High-resolution line-scanning optical coherence microscopy", Opt. Lett. 32, 1971 (2007)[CrossRef] B. Grajciar, Y. Lehareinger, A.F. Fercher, R.A. Leitgeb, "High sensitivity phase mapping with parallel Fourier domain optical coherence tomography at 512 000 A-scan/s", Opt. Exp. 18, 21841 (2010)[CrossRef] M. Choma, A. K. Ellerbee, Ch. Yang, T.L. Creazzo, J.A. Izatt, "Spectral-domain phase microscopy", Opt. Lett. 30, 1162 (2005)[CrossRef] S.M.Bagherzadeh, B. Grajciar, C.K. Hitzenberger, M. Pircher, A.F. Fercher, "Dispersion-based optical coherence tomography OCT measurement of mixture concentrations", Opt. Lett. 32(20), 2924 (2007)[CrossRef]